Discovery of facile amides-functionalized rhodanine-3-acetic acid derivatives as potential anticancer agents by disrupting microtubule dynamics. (1st January 2021) - Zhou, Xiang; Liu, Jiamin; Meng, Jiao; Fu, Yihong; Wu, Zhibin; Ouyang, Guiping; Wang, Zhenchao
Abstract: Microtubule dynamics are crucial for multiple cell functions, and cancer cells are particularly sensitive to microtubule-modulating agents. Here, we describe the design and synthesis of a series of ( Z )-2-(5-benzylidene-4-oxo-2-thioxothiazolidin-3-yl)- N -phenylacetamide derivatives and evaluation of their microtubule-modulating and anticancer activities in vitro . Proliferation assays identified I20 as the most potent of the antiproliferative compounds, with 50% inhibitory concentrations ranging from 7.0 to 20.3 µM with A549, PC-3, and HepG2 human cancer cell lines. Compound I20 also disrupted cancer A549 cell migration in a concentration-dependent manner. Immunofluorescence microscopy, transmission electron microscopy, and tubulin polymerisation assays suggested that compound I20 promoted protofilament assembly. In support of this possibility, computational docking studies revealed a strong interaction between compound I20 and tubulin Arg β 369, which is also the binding site for the anticancer drug Taxol. Our results suggest that ( Z )-2-(5-benzylidene-4-oxo-2-thioxothiazolidin-3-yl)- N -phenylacetamide derivatives could have utility for the development of microtubule-stabilising therapeutic agents. Graphical abstract: UF0001